Japan's Middle East security policy theory and cases - Miyagi, Yukiko (Sheffield Centre for Japanese Studies/Routledge series, 2008)
Focuses on Japanese policy toward Middle East security issues, examining how policy is shaped by the need to both maintain Japan's security alliance with the US and its oil relationship with states in the Middle East.